Application of Atmospheric Non-Thermal Plasmas to Control Rhizopus stolonifer Causing Soft Rot Disease in Strawberry - Dheerawan Boonyawan; Hans Jørgen Lyngs Jørgensen; Salit Supakitthanakorn (Horticulturae)
Rhizopus stolonifer causes soft rot disease in strawberry and is considered one of the most destructive pathogens affecting strawberries worldwide. This study investigated the efficacy of three atmospheric non-thermal plasmas (NTPs) consisting of gliding arc (GA), Tesla coil (TC) and dielectric barrier discharge (DBD) for controlling R. stolonifer infection. Fungal mycelial discs were exposed to these plasmas for 10, 15 or 20 min, whereas conidial suspensions were treated for 1, 3, 5 or 7 min. Morphological alterations following non-thermal plasma exposure were studied using scanning electron microscopy (SEM). Exposure to GA and DBD plasmas for 20 min completely inhibited mycelial growth. SEM analysis revealed significant structural damage to the mycelium, sporangia and sporangiospores of treated samples compared to untreated controls. Complete inhibition of sporangiospore germination was achieved with treatments for at least 3 min for all NTPs. Pathogenicity assays on strawberry fruit showed that 15 min exposure to any of the tested NTPs completely prevented the development of soft rot disease. Importantly, NTP treatments did not adversely affect the external or internal characteristics of treated strawberries. These findings suggest that atmospheric non-thermal plasmas offer an effective approach for controlling R. stolonifer infection in strawberries, potentially providing a non-chemical alternative for post-harvest disease management.